Homegrown terrorism - merely another wave in terrorism or the emergence of a new strategic threat? - Hooi, Edwin. (2009)
The surge in homegrown terrorist attacks in the hardened post-9/11 security environment has led to some commentators to assert that these are indications of Al-Qaeda evolving naturally into a more resilient form to survive. On the other hand, there are increasing signs that homegrown terrorism may be a more sinister threat that hold strategic implications. Such signs include Al-Qaeda's claims of adopting Fourth Generation Warfare strategy and growing awareness of the teachings and writings of a previously unknown Al-Qaeda strategic thinker, Mustafa Setmariam Nassar (MSN). Using the analogy of the creationist-evolutionist debate, this paper will examine these assertions and discuss whether homegrown terrorism is merely another wave in terrorism or a strategic threat with far-reaching consequences.